O uso das alíquotas diferenciadas de IPTU para as áreas de preservação permanente e a função socioambiental da propriedade - Gonçalves, Naíla (My University, 2016)
This dissertation proposes that the Municipalities tax urban areas of permanent preservation with different parameters in relation to the common urban areas, in order to encourage owners of permanent preservation areas. This paper analyzes the conditions for legal reserve compensation that can bring real benefits to nature (environmental implications), while reducing the impact of these measures on private property and / or agricultural / commercial / industrial production (economic implications). In order to carry out this research, it was carried out based on a bibliographical review, official data of the Municipalities, published theses and judicial decisions that have discussed some relevant point of the research. As a result, it was noted the importance of legislative tools for ownership to encompass its socio-environmental function, as well as the Municipality that deliberates the IPTU for an extra-fiscal function in order to protect nature is actually seeking to stimulate or discourage certain relative behaviors to the environment.
Esta dissertação propõe que os Municípios tributem áreas urbanas de preservação permanente com parâmetros diferentes em relação às áreas urbanas comuns, com objetivo de incentivar os proprietários de áreas de preservação permanente. Diante disso, este trabalho analisou as condições para compensações de reserva legal que podem trazer benefícios reais para a natureza (implicações ambientais), enquanto reduz o impacto dessas medidas sobre a propriedade privada e/ou produção agrícola/comercial/industrial (implicações econômicas). Para efetivação desta pesquisa realizou-se com base em revisão bibliográfica, dados oficiais dos Municípios, teses publicadas e decisões judiciais que tenham discutido algum ponto relevante da pesquisa. Como resultado constatou-se a importância das ferramentas legislativas para que a propriedade abarque sua função socioambiental, assim como o Município que delibera o IPTU para uma função extrafiscal com o intuito de proteger a natureza está buscando, na verdade, estimular ou desestimular determinadas condutas relativas ao meio ambiente.
Keywords: Imposto predial e territorial urbano; Direito ambiental; Meio ambiente; Incentivos fiscais; Gestão ambiental; Política pública; Tax Urban Building and Land; Environmental law; Environment; Tax incentives; Public policy; Environmental management